(untitled) (Annals of Medical Research, 2021)
Aim: To present the experiences and results of laparoscopic surgeries we conducted in a year’s time in our clinic.Materials and Methods: A retrospective review of ninety-nine patients who underwent laparoscopic urological surgery between May 2013 and May 2014.Results: There were fifty-eight males and forty-two females in our study. Three of patients were pediatric. Transperitoneal approach was used for 99 patients. Mean age of all patients was 47.2 (2-76) years. The operation type and total numbers undergoing the operation were as follows: simple nephrectomy: 50; renal cyst excision: 11; radical nephrectomy: 10; dismemberred pyeloplasty: 10; ureterolithotomy: 5; adrenalectomy: 3; orchiectomy: 1; orchiopexy: 1; nefroureterectomy with partial cystectomy: 3 (one of these patients was situs inversus totalis); partial nephrectomy: 2; and pyelolithotomy and hemi-nephrectomy 1. No intraoperative complications were experienced and we did not need to switch to open surgery in any of the cases. In three patients preoperatively and in one patient postoperatively blood transfusion was required. Superficial wound infection and dehiscence developed in 4 patients while two patients developed subileus and one incisional hernia. The mean postoperative hospitalization duration was 2.26 (1-4) days.Conclusion: Indication areas and popularity of the laparoscopic procedures in urology are increasing every day. Today, laparoscopic operations have increased frequency compared to open surgery due to shorter hospital stay, less pain, and high patientsatisfaction. Laparoscopic surgery is a safe and feasible technique but it requires necessary experience in peripheral state hospitals.Keywords: Laparoscopy, Nephrectomy, Pyeloplasty, Adrenalectomy.